TINJAUAN PEMOTONGAN PPH PASAL 23 PADA CV BERKAT TIMAH SEJAHTERA - Maria Ave Melkya; Janti Saragih; Fenny BNL Tobing (Buletin Ekonomi, 2018)
In the era of globalization in the world economy is ketat.Itu make us required to have a greater ability to be bersaing.Hal This also occurs in the working world wide. Then the student as a potential fresh graduate would not want to have more ability at the time wanted to start a dive in the world of work later. To meet all necessary improvement of the quality of the workforce that has been ada.Universitas Kristen Indonesia Faculty konomi as one who has experienced the Institute of Education, has the aim to put out more graduates - lusan best. That is not only reliable in the academic field but also have the best possible preparation in the competitive world of work, therefore it is time for the Indonesian people began to fix themselves in the field of economy to seek revenue to be used as an income assets of the largest and most important. Indonesia needs to do a tax reform.Keywords: Taxation, Income Taxes 23, Rental Services, Cutting, Crediting